2023
DOI: 10.1038/s41598-023-29921-1
|View full text |Cite
|
Sign up to set email alerts
|

Mexican traditional medicines for women’s reproductive health

Abstract: Like China, Mexico has a traditional system of medicine dating back almost 5000 years that incorporates the healing practices of pre-Columbian civilizations, including the Maya and Aztec. Mexican Traditional Medicine (MTM) women depend on MTM practices and herbal medicines for their primary healthcare needs as limited access and high costs of Western medicine is a significant problem. The aims of this work were to determine the medicinal plants more commonly used in MTM for women’s reproductive health issues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Over the course of human history, some herbs, plants, and fruits have been used extensively in different cultures and societies to treat injuries, diseases, viruses, and bacterial infections, and even to enhance women's health during pregnancy to facilitate childbirth [16]. In pregnancy, the particular use of plants and herbs is focused mostly on alleviating conditions, such as diarrhea, chills, nausea, constipation, vomiting, or to increase milk production and accelerate labor.…”
Section: Bioactive Compounds Contained In Foods Used During Pregnancymentioning
confidence: 99%
“…Over the course of human history, some herbs, plants, and fruits have been used extensively in different cultures and societies to treat injuries, diseases, viruses, and bacterial infections, and even to enhance women's health during pregnancy to facilitate childbirth [16]. In pregnancy, the particular use of plants and herbs is focused mostly on alleviating conditions, such as diarrhea, chills, nausea, constipation, vomiting, or to increase milk production and accelerate labor.…”
Section: Bioactive Compounds Contained In Foods Used During Pregnancymentioning
confidence: 99%
“…Some plants in traditional Mexican medicine widely utilized by at least four ethnic groups are Aristolochia odoratissima, Citrus aurantium L., Equisetum myriochaetum, Justicia spicigera, Matricaria chamomilla, Piper auritum Kunth, and Sambucus nigra [53]. Most common uses of traditional Mexican medicine are focused on conditions of the digestive system, culture-bound syndromes, genitourinary system, infectious and parasitic diseases, pregnancy, childbirth, and the respiratory system, among others [53][54][55].…”
Section: Potential Of Medicinal Plantsmentioning
confidence: 99%
“…Approximately 85% of healthcare professionals know about herbal medicines, and ~75% recommend their use. 4 Pregnant women make use of TM for several reasons: lack of fetal turning, overdue delivery, breech pregnancy and false labor, morning sickness, abdominal pain, constipation, heartburn, dirty or air-filled uterus, sexually transmitted diseases, and high blood pressure. 5,6 Holst et al 7 found that more than 50% of the pregnant women they studied used herbal remedies.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 85% of healthcare professionals know about herbal medicines, and ∼ 75% recommend their use. 4…”
Section: Introductionmentioning
confidence: 99%